Review of Selected DFAT Facilities: Independent Consultant Report to DFAT, Key Findings - and Pieper, Lynn (DFAT, 2018)
For the purposes of this report, a facility is defined as an aid delivery mechanism that provides flexible (adaptive and responsive) services managed in an integrated way. Objectives (or endof-facility outcomes) are specified, but the pathways to deliver them are left unspecified. The facility is a highly relevant model for delivering Australian aid effectively. Achievement of the Sustainable Development Goals depends on flexible approaches that work across sectors and that integrate significant cross-cutting themes such as gender equality and social inclusion. Efficient DFAT management of a $4 billion aid program requires a shift to fewer and larger initiatives, to make best use of limited internal management resources while still enabling policy and program choices that can have real impact. Facilities and other flexible delivery mechanisms offer significant potential for better development results. They can: enable collaborative and responsive partnership approaches to gain traction; allow activities to experiment and adapt based on progress, demand and contextual changes; and provide the opportunity for outcome-focused coherence across sectors, enabling the whole to be more than the sum of the parts. Facilities are not new, but they are different today. Facilities have existed since at least the mid-1990s. What is new is that some facilities today are very large; and the flexibility they enable is increasingly and consciously being used to strengthen links between the technical and the political, for more effective development results. This is a positive trend, but it adds enormously to their complexity and visibility, creates new risks, and has resulted in role confusion (especially in early years of implementation) between DFAT and its contractors.